2016
DOI: 10.1021/acsami.5b11956
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered Solar-Blind Photodetector with Fast Response Based on Au/β-Ga2O3 Nanowires Array Film Schottky Junction

Abstract: Because of the direct band gap of 4.9 eV, β-Ga2O3 has been considered as an ideal material for solar-blind photodetection without any bandgap tuning. Practical applications of the photodetectors require fast response speed, high signal-to-noise ratio, low energy consumption and low fabrication cost. Unfortunately, most reported β-Ga2O3-based photodetectors usually possess a relatively long response time. In addition, the β-Ga2O3 photodetectors based on bulk, the individual 1D nanostructure, and the film often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
237
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 364 publications
(262 citation statements)
references
References 40 publications
13
237
2
Order By: Relevance
“…This value is comparable to what has been recently reported on self-powered Ga 2 O 3 nanowire based photodetectors50. Besides not requiring an external energy source for operation, photovoltaic mode operation in our case appears to have the additional advantage of generating a better signal-to-noise ratio and higher stability than when a nonzero bias is applied.…”
Section: Resultssupporting
confidence: 87%
“…This value is comparable to what has been recently reported on self-powered Ga 2 O 3 nanowire based photodetectors50. Besides not requiring an external energy source for operation, photovoltaic mode operation in our case appears to have the additional advantage of generating a better signal-to-noise ratio and higher stability than when a nonzero bias is applied.…”
Section: Resultssupporting
confidence: 87%
“…It has been widely used as photocatalyst, solar-blind UV detectors, gas sensors, and short wavelength light emitting diodes34567. Besides, it is a promising candidate for power devices as higher Baliga’s figures of merit (over 3000) and higher breakdown field (8 MV/cm), a lower cost and more easily accessible properties compared with the conventional power semiconductors such as SiC and GaN891011.…”
mentioning
confidence: 99%
“…Most β‐Ga 2 O 3 nanostructure‐based photodetectors are photoconductive with a relatively slow response speed due to the persistent photoconductivity effect . Hybrid structures, such as Au/Ga 2 O 3 , SiC/β‐Ga 2 O 3 film, and Ga 2 O 3 /SnO 2 core‐shell nanowires, display improved performance . Fang's group reported that ZnO‐Ga 2 O 3 core‐shell heterostructures were fabricated into a self‐powered solar‐blind photodetector (200‐280 nm), as illustrated by the energy band diagram (Figure A,B).…”
Section: Nanowire Photodetectorsmentioning
confidence: 99%